Financial Literacy in Nepal: A Survey Analysis from College Students - Thapa, Bharat Singh; Nepal, Surendra Raj (NRB Economic Review, 2015)
This study surveys 436 college students to examine their financial literacy; the impact of demographic, educational and personality characteristics on financial literacy. Mean, ANOVA and logistic regression were used in carrying out analysis. Results show that most of the students have basic level of financial knowledge but they lack in understanding of credit, taxes, share market, financial statement and insurance. Students are highly influenced by their parents at home and they have positive attitude towards savings. The study further identified income, age, stream of education, types of college, and attitude of students as determinants of financial knowledge; and financial knowledge is unaffected by gender, university affiliation, financial behavior and influence. It is concluded that college students have basic level of financial knowledge. However, overall financial knowledge of the students is affected by some of their demographic, educational and personality characteristics.